The Impacts of Fermentation and Varied Leavening Agents on Phytic Acid Degradation and Mineral Nutritional Quality of Conventional Pakistani Flat Wheat Breads - Ghaffar, Fazia (Indus Journal of Bioscience Research, 2025)
Introduction: Wheat bread is a staple Pakistani food, and whole grain is generally thought of as being healthier than white bread due to its higher dietary fiber, vitamins, and many important minerals. However, wholegrain bread also contains high levels of phytate, which may bind desirable nutrients, preventing their absorption in the gut and thereby reducing the efficacy of the end product. Fermentation has been shown to decrease the amount of phytate in wholegrain cereals. The indigenous methods of leavening may be a potential biofriendly way of enhancing the nutritional quality of local wheat breads. Methods: The study aimed to evaluate the impact of heat processing on phytic acid, mineral content, and mineral solubility of conventional wheat breads. Six types of wheat flours were selected, including fine wheat flour, chakki wheat flour, maida, whole wheat flour, and granulated wheat flour. Initially, the raw flour was analyzed for percent phytate, phosphorus, and iron concentrations. Three types of breads: chapatti, flat bread made on an iron skillet, and tandoori roti (conventional hot oven), after preparing doughs as unleavened, fermented with bicarbonate soda, commercial yeast, and sourdough culture. All types of breads were analyzed for percent phytate, percent phytate degradation, mineral content, and mineral solubility as per standard procedures. Results: The results showed that raw fine wheat flour had the highest phytic content, while unleavened categories had the highest phytic acid content. The sourdough cultured leavened flour, the highest levels were observed as tawa Roti at 0.67% ± 3.30, chapatti at 0.99% ± 2.44, and tandoori Roti at 1.15% ± 2.29. The percentage degradation of phytate in fine wheat flour was highest in sourdough cultured tandoori roti at 61.8 %, followed by sourdough tawa roti at 61.0% and yeast tandoori roti at 60.47. The per cent degradation of phytate in Chakki wheat flour breads was highest in sourdough cultured tandoori roti (75.3), tawa Roti (70.1%), chapatti (57.5) and for the yeast fermented roti ithe higher degradation occurred in chapatti (55.4), tandoori roti (51.8) and tawa roti (48.2). soda tawa Roti (67.6 %), and yeast chapatti (0.3 %). Doughs leavened with soda also showed appreciable degradations. The percent degradation of phytate in maida wheat flour was highest in sourdough cultured tandoori roti (79.8%), tawa roti (69.5%), and chappati (58.5). The percent degradation of phytate in whole wheat flour was highest in sourdough cultured tandoori roti 57.7%, followed by tawa roti 47.6%, and chapatti 45.3%. Fermentation with the addition of bicarbonate soda also resulted in degradation. The unleavened breads showed the least reduction. The effects of fermentation were positive on both mineral content and mineral solubility. Conclusion: The current study concludes that the conventional method of making fermented wheat breads degrades phytate significantly while improving the mineral nutrition of these breads.